2017
DOI: 10.17269/cjph.108.5848
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sexual orientation and health in Canada: Who are we capturing and who are we missing using the Statistics Canada sexual orientation question?

Abstract: OBJECTIVE: Public health research on inequalities in Canada depends heavily on population data sets such as the Canadian Community Health Survey. While sexual orientation has three dimensions -identity, behaviour and attraction -Statistics Canada and public health agencies assess sexual orientation with a single questionnaire item on identity, defined behaviourally. This study aims to evaluate this item, to allow for clearer interpretation of sexual orientation frequencies and inequalities. METHODS:Through an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Although same-sex behavior and homosexuality were often used interchangeably in the literature, empirical studies have revealed discordance between self-reported sexual identity and sexual behaviors (Savin-Williams, 2006). For example, some men engage in same-sex behaviors, but they do not necessarily identify themselves as gay ( Dharma & Bauer, 2017 ). The same-sex behavior of the MSM population was the main interest in this review to cover both homosexual and nonhomosexual orientations mainly because of its broader behavioral implication in the context of HIV infection and transmission.…”
Section: Methodsmentioning
confidence: 99%
“…Although same-sex behavior and homosexuality were often used interchangeably in the literature, empirical studies have revealed discordance between self-reported sexual identity and sexual behaviors (Savin-Williams, 2006). For example, some men engage in same-sex behaviors, but they do not necessarily identify themselves as gay ( Dharma & Bauer, 2017 ). The same-sex behavior of the MSM population was the main interest in this review to cover both homosexual and nonhomosexual orientations mainly because of its broader behavioral implication in the context of HIV infection and transmission.…”
Section: Methodsmentioning
confidence: 99%
“…According to the 2015 Canadian Community Health Survey, 1.7% of people between 18 and 59 years old identified themselves as gay or lesbian and 1.3% of people in that age range identified as bisexual (Statistics Canada, 2016 ). The Canadian Community Health Survey does not include trans populations and likely underestimates all queer communities, as is often the case with groups of stigmatized people (Clark et al, 2018 ; Dharma & Bauer, 2017 ).…”
Section: Current Policy and Funding Environment In Ontariomentioning
confidence: 99%
“…The full extent of health inequities experienced by the LGBTQ+ community is likely not fully understood. Dharma and Bauer ( 2017 ) found flaws in definitions and measures of sexual identity in Canadian health surveys; these surveys may not capture the nuances of sexual behaviours and gender identity and expression. (See also Cahill & Makadon, 2017 ; Wolff et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional, mixed-methods data were collected between October 2015 and March 2016 (Bauer et al 2017;Dharma and Bauer 2017). Residents of Canada aged 14 or older with the ability to complete an online English-language survey were eligible to participate.…”
Section: Sampling and Recruitmentmentioning
confidence: 99%